HEALTH AND SAFETY DISCLOSURES PRACTICE IN INDONESIAN CHEMICAL INDUSTRIES : A QUALITATIVE CONTENT ANALYSIS STUDY - Laoli, Warman Berkat; Davianti, Arthik (International Journal of Social Science and Business, 2019)
This study aims to determine the disclosure for occupational health and safety, as presented in GRI Standard-based CSR. A qualitative approach with content analysis was applied in the study. Content analysis is an analysis based on narrative according to certain criteria which classified through keywords and referred to as disclosure groups. The study focused on companies listed in Indonesia, in the chemical sector. The content analysis examined eleven companies. The results showed that based on the disclosures, all companies had implemented health and safety. Further, it also suggested that the disclosures were not necessary for accordance with GRI Standard.